Asma grave refratária e bronquiolite obliterante pós-infecciosa em crianças e adolescentes: como diferenciá-las quanto aos aspectos tomográficos, funcionais e de marcadores não invasivos do processo inflamatório? - Raquel Vidica Fernandes (2013)
Introduction: The clinical differentiation between severe asthma and bronchiolitis obliterans is sometimes a challenge, because of a possible overlap of clinical symptoms, radiological and functional parameters, and both are chronic obstructive pulmonary diseases. Objectives: Review the principal tomographic and functional alterations of severe asthma and bronchiolitis obliterans. Data source: A non-systematic review of the literature from 1990 to 2013 was carried out using the databases LILACS, Medline, HighWare, Scielo and Pubmed. Data synthesis: The tomographic changes more frequently found in children and adolescents with bronchiolitis obliterans were bronchiectasis and mosaic attenuation. In severe asthma, the alteration most frequently found were bronchial wall thickening and air trapping. Concerning to functional aspects, in BO has been described a pattern of chronic obstruction to airflow associated to inflammatory lesion of small airway. In severe asthma is also observed obstructive lung disease, reversible or fixed. In the only two studies found in literature any of them encompassing only children and adolescents - comparing these diseases was seen as changes most found: bronchiectasis, bronchial wall thickening, mosaic attenuation and air trapping. When it came to relation to functional parameters, this two studies found statistically significant differences mostly in relation to FVC and RV/TLC between this two diseases. Conclusions: In the articles found, it was observed that severe asthma and bronchiolitis obliterans presents overlap of functional and tomography alterations. Value of FEF25-75% below to 30% and the presence of bronchiectasis and mosaic attenuation, in most of the studies, speak in favor of bronchiolitis obliterans.